Vertical distribution of macrobenthic communities from a shipwreck in the Strait of Magellan - Velasco-Charpentier, Catalina; Pizarro-Mora, Felipe; Navarro Martinez, Nelso Patricio; Morales-Torres, Diego F.; Valdivia, Nelson (My University, 2021)
Abstract: Shipwrecks are artificial reefs that can enhance local diversity. In this study, the macrobenthic community associated with a shipwreck in the Strait of Magellan, the DAP Mares, is described for the first time. Species richness and functional group richness were estimated, and general linear models were used to test the prediction that diversity varied systematically with depth. The most speciose and abundant groups were echinoderms, molluscs, sponges, and tunicates. The most abundant trophic type was suspension feeders. Species richness changed significantly with depth, being similar between the upper and middle zones but decreasing at the deepest zone. Neither functional group richness nor functional dispersion (Rao's quadratic entropy) varied with depth, suggesting that not all aspects of macrobenthic diversity respond equally to this variable. The biodiversity observed was consistent with that described for natural hard substrates in the Strait of Magellan. Thus, this vessel could represent a good model to study patterns of community structure.
Keywords: biodiversity; benthic communities; artificial reef; patagonia